IMPLEMENTASI PPH FINAL PASAL 15 PADA PT. PELAYARAN DUTA LINTAS SAMUDERA BERDASARKAN UU NO.36 TAHUN 2008 - -, Dewi Rukmana (EKONOMIA, 2017)
Purpose of this study was to analyze whether or not the income tax according to PT. Pelayaran Duta Lintas Samudera based shipping Tax Law Clause 15 – Law No. 36 in 2008 Analyzer used the comparative method method is done by comparing according to Regulation Act – Income Tax Law Clause 15 of Law – Law No.36 in 2008 Based on the results of the analysis that has been presented, it can be seen that the implementation of the income tax that has been carried out by PT. Pe,ayaran Duta Lintas Samudera Samarinda in accordance with Clause 15 of Income Tax Act 36 of 2008 although there are obstacles income tax provision of 15 piecesof evidence by the customer / tenant vessel does not affect the imposition of the tariff Income Tax Clause 15 evidenced by the absence of change in the calculation / imposition if income tax clause 15. Situation reflects the implementation of the income tax on the PT. Pelayaran Duta Lintas Samudera has been running based on Clause 15 of Income Tax Act 36 0f 2008.